2009
DOI: 10.1203/pdr.0b013e31819984ce
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mouse Model of Ureaplasma-Induced Perinatal Inflammation: Effects on Lung and Brain Injury

Abstract: Chorioamnionitis is associated with increased lung and brain injury in premature infants. Ureaplasma is the microorganisms most frequently associated with preterm birth. Whether Ureaplasma-induced antenatal inflammation worsens lung and brain injury is unknown. We developed a mouse model combining antenatal Ureaplasma infection and postnatal oxygen exposure. Intraamniotic Ureaplasma Parvum (UP) increased proinflammatory cytokines in placenta and fetal lungs. Antenatal exposure to UP or broth caused mild postna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 36 publications
4
83
1
1
Order By: Relevance
“…In an antenatal mouse model of ureaplasma colonization with signs of perinatal inflammation, there was proinflammatory cytokine activation (MCP-1, IL-1␤, and IL-6) and ureaplasma colonization cleared by postnatal day 3.5 (37). These mice had an increased inflammatory response to hyperoxia relative to uninfected mice (37). In our study, UP exposed lambs and controls had similar PaO 2 and oxygenation, and proinflammatory cytokine mRNA levels were not different.…”
Section: Table 2 Markers Of Lung Inflammation and Injurysupporting
confidence: 48%
“…In an antenatal mouse model of ureaplasma colonization with signs of perinatal inflammation, there was proinflammatory cytokine activation (MCP-1, IL-1␤, and IL-6) and ureaplasma colonization cleared by postnatal day 3.5 (37). These mice had an increased inflammatory response to hyperoxia relative to uninfected mice (37). In our study, UP exposed lambs and controls had similar PaO 2 and oxygenation, and proinflammatory cytokine mRNA levels were not different.…”
Section: Table 2 Markers Of Lung Inflammation and Injurysupporting
confidence: 48%
“…For example, high-dose LPS delivered late in gestation (ED 14-17) induces preterm labor associated with placental and fetal inflammation (38)(39)(40), whereas heat-killed Escherichia coli induces preterm labor and uterine inflammation, without changes in placental or fetal cytokines (41,42). In contrast, infection with Ureaplasma late in gestation induces placental and fetal inflammation without preterm labor (43), whereas viral infection early in gestation (ED 8.5) triggers fetal and maternal splenic inflammation, without inducing placental inflammation or preterm labor (44). In this study, we delivered the Nod1 agonist iE-DAP late in gestation (ED 14.5) and found that, at a high dose of 1000 mg, preterm delivery was induced.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxides are markedly increased in brain tissues of animals exposed to hyperoxia (11). Oxidant stress and systemic inflammation each have independent and synergistic deleterious apoptotic effects on brain microglial cells and immature oligodendrocyte (12)(13)(14). Notably, prolonged supplemental oxygen exposure and systemic inflammation as measured by plasma levels of IL-6 and IL-8 have both been strongly associated with adverse long-term pulmonary and neurodevelopmental outcomes in preterm infants (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%